2012
DOI: 10.2119/molmed.2012.00205
|View full text |Cite
|
Sign up to set email alerts
|

CSE1L, a Novel Microvesicle Membrane Protein, Mediates Ras-Triggered Microvesicle Generation and Metastasis of Tumor Cells

Abstract: Tumor-derived microvesicles are rich in metastasis-related proteases and play a role in the interactions between tumor cells and tumor microenvironment in tumor metastasis. Because shed microvesicles may remain in the extracellular environment around tumor cells, the microvesicle membrane protein may be the potential target for cancer therapy. Here we report that chromosome segregation 1-like (CSE1L) protein is a microvesicle membrane protein and is a potential target for cancer therapy. v-H-Ras expression ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
55
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 50 publications
2
55
0
Order By: Relevance
“…A recent report on B16F10 melanoma cells showed that CSE1L overexpression triggered microvesicle generation, whereas CSE1L knockdown diminished Ras-induced microvesicle generation, MMP-2/MMP-9 secretion, and metastasis [33]. Recent studies have proposed that secretory CSE1L might be a potential prognostic marker of cancer [33,40,41,43]. This study further showed that cytoplasmic CSE1L was involved in the invasiveness of CRC cells.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…A recent report on B16F10 melanoma cells showed that CSE1L overexpression triggered microvesicle generation, whereas CSE1L knockdown diminished Ras-induced microvesicle generation, MMP-2/MMP-9 secretion, and metastasis [33]. Recent studies have proposed that secretory CSE1L might be a potential prognostic marker of cancer [33,40,41,43]. This study further showed that cytoplasmic CSE1L was involved in the invasiveness of CRC cells.…”
Section: Discussionsupporting
confidence: 57%
“…The results indicate that CSE1L plays a role in regulating the metastasis of colorectal cancer cells. Moreover, CSE1L is known to stimulate the extension of invadopodia and the secretion of matrix metalloproteinases of several cancer cell lines [15,33]. Thus, stimulation of tumor invasion and metastasis should be the correct role of CSE1L in tumor development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that CSE1L is related to microvesicle biogenesis and causes temporary extension of the plasma membrane which contributes to cancer cell migration and invasion [20]. Moreover, increased CSE1L expression enhances the secretion of matrix metalloproteinase-2 and the invasiveness of cancer cells [20].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, increased CSE1L expression enhances the secretion of matrix metalloproteinase-2 and the invasiveness of cancer cells [20]. Furthermore, reduction in CSE1L expression resulted in metastasis inhibition in B16 and F10 melanoma cells in mice [21], and overexpression of CSE1L in MCF-7 breast cancer cells increased the migration and invasiveness of cancer cells [20]. CSE1L is mapped on chromosome 20q13 which is known to harbor amplifications that correlate with aggressive breast cancer [22].…”
Section: Discussionmentioning
confidence: 99%